Peranan Kepercayaan Kepada Penjual Dan Label Halal Terhadap Minat Beli Daging Halal - Sumadi Sumadi (Benefit: Jurnal Manajemen dan Bisnis, 2016)
This aimed of this study is to explain the empiricly of factors that influence the purchase intention of halal-meat by Moslem consumers. This research used Fishbein and Ajzen’s Theory of  Reasoned Action (TRA) as a model. There are four latent variables that being used to construct this model. Purchase intention of halal-meat was predicted to be influenced by attitude, salesperson trust and halal label. While the salesperson trust and halal label was the antecedent that influence the attitude of halal-meat. The method used halal-meat as the object, population that used are adult or married Moslem consumers in Indonesia with the sample is women buyer. Data collected used convenience approach. The sample was 300 respondents in Yogyakarta, Surabaya and Jakarta.Empirical data analyzed with Structural Equation Model (SEM) Amos. The research result explained that there is positive and significant influence between  salesperson trust and label-halal toward attitude, and attitude is positive and significant influence purchase intention of halal-meat. While, the salesperson trust had significant negatively toward purchase intention of halal-meat. In other side halal-label is not significantly influence consumer’s attitude toward halal-meat. PERANAN KEPERCAYAAN KEPADA PENJUAL DAN LABEL HALALTERHADAP MINAT BELI DAGING HALAL